E-business and Telecommunications 4th International Conference, ICETE 2007, Barcelona, Spain, July 28-31, 2007, Revised Selected Papers - Filipe, Joaquim; Obaidat, Mohammad S. (Communications in Computer and Information Science, 2009)
This book constitutes the best papers of the 4th International Conference on E-business and Telecommunication Networks, ICETE 2007, held in Barcelona, Spain, during July 28-31, 2007. The 26 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 418 submissions. The papers are organized in four parts according to their conferences: ICE-B, SECRYPT, SIGMAP and WINSYS.